Pembentukan Iklim Kelas Positif dalam Pembelajaran PAI di MI Ahmad Maryam Surakarta - Hermawan, Rudi; Subando, Joko (Lembaga Yasin AlSys, 2026)
Islamic Religious Education (PAI) learning at the Madrasah Ibtidaiyah level plays a strategic role in shaping students’ religious character and noble morals, and its success is determined not only by mastery of religious content but also strongly influenced by the classroom climate created throughout the learning process. This study aimed to describe the classroom climate conditions in PAI learning, the teachers’ efforts and strategies in developing a positive classroom climate, and the supporting and inhibiting factors affecting the formation of a positive classroom climate in PAI learning at MI Ahmad Maryam Surakarta. The study employed a qualitative approach with a descriptive design, involving PAI teachers and students as participants; data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the classroom climate in PAI learning tended to be conducive and religious, as reflected in humanistic interactions between teachers and students, a comfortable learning atmosphere, and the cultivation of religious values through role modelling and habituation. Teachers’ efforts and strategies to build a positive classroom climate were realized through classroom management grounded in Islamic values, the use of varied and participatory teaching methods, and the implementation of positive discipline. Supporting factors included teachers’ competence and personality, support from the madrasah environment, and parental involvement, while inhibiting factors comprised differences in students’ characteristics, limited facilities and infrastructure, and the influence of the social environment outside the madrasah. This study concludes that developing a positive classroom climate is an ongoing process that requires synergy among teachers, the madrasah, and families to improve the quality of PAI learning and strengthen students’ religious character formation.